To solve this system of equations, we can use either substitution or elimination. Let's use the elimination method.
Given equations:
-3x + 5y = 21 ....(1)
6x - y = -15 ....(2)
To eliminate y, we can multiply equation (2) by 5:
5(6x - y) = 5(-15)
30x - 5y = -75 ....(3)
Now, we can add equation (1) and equation (3) to eliminate y:
-3x + 5y + 30x - 5y = 21 - 75
27x = -54
x = -2
Now, substitute x = -2 back into equation (2) to find the value of y:
6*(-2) - y = -15
-12 - y = -15
-y = -15 + 12
-y = -3
y = 3
Therefore, the solution to the system of equations is x = -2 and y = 3.
🏆 #5.%0D%0AWhat is the solution to this system of equations?%0D%0A%0D%0A%0D%0A%0D%0A −3x+5y=21%0D%0A%0D%0A 6x−y=−15
1 answer